2020
DOI: 10.2147/dmso.s244432
|View full text |Cite
|
Sign up to set email alerts
|

<p>Integrated Datasets of Proteomic and Metabolomic Biomarkers to Predict Its Impacts on Comorbidities of Type 2 Diabetes Mellitus</p>

Abstract: The objective of the current study is to accomplish a relative exploration of the biological roles of differentially dysregulated genes (DRGs) in type 2 diabetes mellitus (T2DM). The study aimed to determine the impact of these DRGs on the biological pathways and networks that are related to the associated disorders and complications in T2DM and to predict its role as prospective biomarkers. Methods: Datasets obtained from metabolomic and proteomic profiling were used for investigation of the differential expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 63 publications
(86 reference statements)
1
11
0
1
Order By: Relevance
“… 22 Several studies demonstrated that hsCRP seems to be the single biomarker of inflammation observed to consistently decreased after bariatric surgery. 23 , 24 Furthermore, the present study demonstrated a decrease of pro-inflammatory cytokines of TNF-alpha and IL-6, which is coherent with previous studies, 15 , 17 while other studies demonstrated no changes. 18 , 19 The inconsistent results of inflammatory cytokines profile between different studies could be due to the degree of insulin resistance at baseline, inflammatory markers’ expression, sample size, study design, technical assays, the timing of assessment of postoperative outcomes, and inherited factors of the study population, which could impact the heterogeneity among the studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“… 22 Several studies demonstrated that hsCRP seems to be the single biomarker of inflammation observed to consistently decreased after bariatric surgery. 23 , 24 Furthermore, the present study demonstrated a decrease of pro-inflammatory cytokines of TNF-alpha and IL-6, which is coherent with previous studies, 15 , 17 while other studies demonstrated no changes. 18 , 19 The inconsistent results of inflammatory cytokines profile between different studies could be due to the degree of insulin resistance at baseline, inflammatory markers’ expression, sample size, study design, technical assays, the timing of assessment of postoperative outcomes, and inherited factors of the study population, which could impact the heterogeneity among the studies.…”
Section: Discussionsupporting
confidence: 92%
“…The current data demonstrated that the anti-inflammatory markers, for instance, adiponectin and IL-10, were increased after LGS in the obese subjects, consistent with several studies that reported similar findings of these markers after bariatric surgery. 15 , 20 A previous study by Kalra et al 2017, demonstrated that plasma leptin level increases with the fat deposition in obese subjects, and a state of leptin resistance is observed in morbidly obese subjects due to the failure of signaling to the hypothalamic satiety center. 21 The present study demonstrated a significant reduction of leptin after 12 weeks of LGS, observed after bariatric surgery in other studies such as gastric plication, bypass, and gastric sleeve.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Patients with COVID-19 also exhibit elevation of other inflammatory markers, such as D-dimer, ferritin and IL-6 (ref. 43 ), which might contribute to an increased risk of microvascular and macrovascular complications originating from low-grade vascular inflammation in patients with underlying diabetes mellitus 44 . In a nationwide study in France, microvascular and macrovascular complications of diabetes mellitus were significantly associated with increased risk of mortality in patients with COVID-19 (ref.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…In the CORONADO study from France, chronic microvascular and macrovascular complications of diabetes were significantly associated with increased risk of mortality in patients with COVID-19 ( 48 ). Elevated inflammatory markers such as D-dimer, ferritin and IL6 may also contribute to an increased risk of chronic diabetic complications in patients with pre-existing DM ( 49 ). Presence and progression of diabetic complications were not systematically evaluated in our study.…”
Section: Discussionmentioning
confidence: 99%